Improvement of Coral Sand With MICP Using Various Calcium Sources in Sea Water Environment - Peng, Jie; Cao, Tianci; He, Jia; Dai, Di; Tian, Yanmei (Frontiers in Physics, 2022)
Microbial-induced calcium carbonate precipitation (MICP) is a promising technique for strengthening soil. The influences calcium sources (calcium chloride, calcium acetate, and calcium nitrate) and seawater/freshwater environment on the improvement of coral sand were studied. A Microbially Induced Carbonate Precipitation (MICP) aqueous solution experiment was carried out to explore the influence of the different calcium source and seawater/freshwater on the relationship between calcium carbonate precipitation and time . Coral sand column treatment tests were conducted to investigate the environmental impact on soil strengthening. The results showed that calcium carbonate production was 20% lower in seawater than that in freshwater. Calcium chloride was found to be the optimal calcium source in terms of the seawater environment affect 2% of calcium carbonate production compared with the freshwater environment. The results of tests on three different calcium sources (calcium chloride, calcium acetate, and calcium nitrate) showed that seawater adversely affected the unconfined compression strength (UCS) and the tensile splitting strength (TSS) of enhanced coral sand columns compared with freshwater. The UCS and TSS values in the freshwater environment were approximately 30-45% higher than those in the seawater environment. Nevertheless the enhanced coral sand columns in the seawater environment exhibited high strength, and the MICP improvement effect can be guaranteed. Therefore, The MICP technology can be used to improve coral sand for construction work in seawater environments.